Heterogeneous porosity distributions of polymer electrolyte membrane fuel cell gas diffusion layer materials with rib-channel compression. (7th September 2016) - Banerjee, R.; Hinebaugh, J.; Liu, H.; Yip, R.; Ge, N.; Bazylak, A.
Abstract: In this study, X-ray Computed Tomography (X-CT) is used to study the structure of the bi-layered gas diffusion layer (GDL) of polymer electrolyte membrane (PEM) fuel cells. This work presents a unique, calibrated segmentation procedure developed in-house to identify the distinct components of the bi-layer GDL, isolating the carbon fibre, the microporous layer and the void regions as individual phases. The novel use of the areal mass and areal volume of the GDL facilitates calibrated, reliable and repeatable multi-component segmentation and removes the high degree of subjectivity that might otherwise be encountered in typical thresholding procedures. Samples with and without MPLs are studied for the impact of rib – channel compression on porosity profiles. Under the channel, the porosity profile is nearly identical to the uncompressed profile. Under the land region, there is a significant decrease in the GDL thickness. It is also observed that the majority of the compression is exhibited by the substrate region while the MPL undergoes significantly reduced compression. Highlights: Novel segmentation methodology for X-ray computed tomographic images of gas diffusion layers. Calibrated segmentation based on areal mass and areal volume of gas diffusion layers. Channel compression has negligible impact on porosity distribution. Rib compression results in fibrous substrate compression with negligible microporous layer compression.